Reformulation of Minimum Wage Policy and Its Implications Concerning Justice and Workers' Welfare in the Context Indonesian law - Kunarti, Siti; Hartini, Sri; Syarafina Dyah Amalia; Pradana, Adhitia; Bahar Elfudllatsani (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
This research addresses the critical necessity of reassessing minimum wage policies with a spotlight on their effects on workers’ justice and welfare. Through the examination of existing policy trends and frameworks for setting wages, the study aims to advocate for a more equitable wage formula that strengthens the government’s role in safeguarding worker interests while ensuring business sustainability. A significant aspect of this investigation is the recent change in wage-setting authority brought about by Government Regulation No. 51 of 2023, which shifts wage-setting power back to a centralized position. Current legal wage policies are not benefiting workers sufficiently, calling for a comprehensive review to design a fair and effective wage framework. The results indicate that with the aim of fairness, the existing minimum wage structure does not guarantee adequate welfare for workers. The study also points out the constrained flexibility of the “alpha” parameter, limiting the wage negotiations between employers and unions to a narrow range of 0.1-0.3. By shedding light on the shortcomings of this policy, this research emphasizes the urgent need for a revised wage formula that genuinely reflects workers’ welfare, representing a shift towards reconciling economic goals with social equity within formal wage policies. An equitable wage should align with the value of the work performed, factoring in difficulty levels, responsibilities, and required skills, while not being below the regional minimum wage.